2022
DOI: 10.3390/su14053116
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Rainfed Maize (Zea mays L.) Production Using Choice of Corn Variety and Nitrogen Scheduling

Abstract: Interestingly more than 50% of the world’s area is rainfed and approximately 80% of maize is cultivated under rainfed condition where selection of cultivar and management of nitrogen have major impact on production. The aim of this study was to evaluate the growth, phenology, yield and quality parameters of maize as influenced by variety and nitrogen scheduling under rainfed condition. For this, a field experiment having two factors was laid out in a factorial randomised block design and replicated three times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The various uses of corn as food, fodder, animal feed, and lately biofuel have further made it a more favorable and valuable crop. Worldwide, on 197.20 million hectares of land, 1148.48 million metric tonnes of maize were harvested, on average [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The various uses of corn as food, fodder, animal feed, and lately biofuel have further made it a more favorable and valuable crop. Worldwide, on 197.20 million hectares of land, 1148.48 million metric tonnes of maize were harvested, on average [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tubers yield/ha were recorded between T1 (16.59 t/ha) and T8 (30.57 t/ha). Data indicated total tubers yield highest in T8 (30.57 t/ha), followed by T7 (29.88 t/ha) that are comparable with [6,[24][25][26] who showed that 'Spunta' cv. produced higher unmarketable tuber than 'Diamant' and 'Cara'.…”
Section: Total Yield Of Tubers / Ha (T)mentioning
confidence: 99%
“…The highest yield was observed when supplying Zn plus Mn foliar combination one time every two weeks (18.32 . 'Spunta' cv produced the highest yield of marketable tuber when supplied with Zn plus Mn foliar combination one time every two weeks, while 'Cara' cv recorded the least yield of marketable tubers when no Zn plus Mn foliar combination was supplied" [6,24,26]. As well as [7, 25,27] stated that "potato is relatively sensitive to Zn deficiency.…”
Section: Total Yield Of Tubers / Ha (T)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rainfed agriculture is widespread throughout the world, including tropical regions, with around 80% of cropland under rainfed cultivation [ 1 ]. Maize ( Zea mays ) is a major food, forage, and fuel crop that is grown on about 207 million hectares of land in over 110 countries [ 2 ], with more than 80% of the area being rainfed [ 3 ]. As a tropical country, Thailand has a majority area of maize under a rainfed system [ 4 ], about 78% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%